Factors, Influencing the Emergence of Child Speech Disorder - Miltiņa, Irēna; Augstkalne, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Speech disorders can have various causes, expression of the pathological processes and severity. Studies in Latvia show that already in early childhood bothlanguage development deficiency and language development delay are evident.These phenomena continue also in the pre-school age where in 30 – 60% of cases show nonconformity of speech and language development to the set norms for the particular age.The established facts illustrate the importance of learning about the causes of speech disorder, because the disorders in sound pronunciation and phonematic perception, as well as insufficient vocabulary affect both the acquisition of pupil’s reading and writing skills and the understanding of verbal instructions.